2019
DOI: 10.1021/acs.est.9b05621
|View full text |Cite
|
Sign up to set email alerts
|

Off-Site Flux Estimates of Volatile Organic Compounds from Oil and Gas Production Facilities Using Fast-Response Instrumentation

Abstract: Flux estimates of volatile organic compounds (VOCs) from oil and gas (O&G) production facilities are fundamental in understanding hazardous air pollutant concentrations and ozone formation. Previous off-site emission estimates derive fluxes by ratioing VOCs measured in canisters to methane fluxes measured in the field. This study uses the Environmental Protection Agency’s Other Test Method 33A (OTM 33A) and a fast-response proton transfer reaction mass spectrometer to make direct measurements of VOC emissions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…29 In contrast, the arithmetic mean (95% CI) of BTEX emission is 0.4 (0.1−0.6) kg/h, which is much higher than the arithmetic mean of 0.09 (0.003−0.38) kg/h found in UGRB. 13 We hypothesize that the great discrepancy is partly caused by the presence of several large BTEX emitters found in this study since we focused on the top ∼50% emitters. Previous work has found that the mean methane emissions (both absolute and productionnormalized) were higher in the Eagle Ford Basin than that in the UGRB.…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations
“…29 In contrast, the arithmetic mean (95% CI) of BTEX emission is 0.4 (0.1−0.6) kg/h, which is much higher than the arithmetic mean of 0.09 (0.003−0.38) kg/h found in UGRB. 13 We hypothesize that the great discrepancy is partly caused by the presence of several large BTEX emitters found in this study since we focused on the top ∼50% emitters. Previous work has found that the mean methane emissions (both absolute and productionnormalized) were higher in the Eagle Ford Basin than that in the UGRB.…”
Section: Resultsmentioning
confidence: 76%
“…This is slightly more skewed than the observed distribution in the UGRB, where the top 20% of sites were responsible for 67% of BTEX emissions. 13 Again, the fact that this study focused on the top ∼50% emitters would naturally reduce the skewness as compared to an unbiased sampling. More importantly, an overlap was found between large emitters, such that the top 20% well pads ranked according to methane emissions were responsible for 79% of total VOCs (C4−C12), 78% BTEX, and 60% methane emissions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…where C p is the peak concentration from the Gaussian fit, U m is the mean wind speed, σ z and σ y are the vertical and lateral plume dispersion that can be determined from the meteorological conditions, such as the Pasquill-Gifford stability classification curves [128] (see Figure 5). The accuracy of the OTM33A method is explored in [129,130].…”
Section: Point Source Gaussian (Psg)-otm33amentioning
confidence: 99%